GAMBARAN TINGKAT PENGETAHUAN KESEHATAN GIGI DAN MULUT DENGAN METODE PENYULUHAN CERITA DAN DEMONSTRASI PADA SISWA/I KELAS IV SD KEMALA BHAYANGKARI 1 MEDAN - SIMAREMARE, ASNITA BUNGARIA; Sondang; Rizka Mahpuza Marbun (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Dental and oral health is very important to maintain, because teeth and gums that are not cared can cause pain, chewing disorders and can even interfere with other part of body health. Increasing knowledge of dental and oral health can be achieved through dissemination using the story and demonstration method where respondents will more easily understand what is conveyed, besides that respondents will also be more impressed because they see and are directly involved when invited to demonstrate an activity. This research is a descriptive study, xamining 32 grade IV students at Kemala Bhayangkari 1 Elementary School, Medan as samples, and aiming to determine the level of students' knowledge about dental and oral health through dissemination using story and demonstration methods. Student knowledge data were collected through questionnaires. The results showed that the level of knowledge of students about dental and oral health before dissemination was 7 people (21.8%) in good criteria, 23 people (71.8%) in medium criteria, and 2 people (6.25%) in poor criteria; while after the dissemination, 32 people (100%) had a good level of knowledge. The conclusion from this study is that the dissemination of oral health through storytelling and demonstration methods can increase students' interest and understanding of oral health. It is important to carry out promotive actions for dental and oral health through the School Dental Health Efforts (UKGS) program in collaboration with the Public Health Center.